2023
DOI: 10.5267/j.ijiec.2022.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-decision points model to solve coupled-task scheduling problem with heterogeneous multi-AGV in manufacturing systems

Abstract: Automated guided vehicle (AGV) is widely used in automated manufacturing systems as a material handling tool. Although the task scheduling problem with isomorphic AGV has remained a very active research field through the years, too little work has been devoted to the task scheduling problems with heterogeneous AGVs. A coupled task with heterogeneous AGVs is a complex task that needs the cooperation of more than one type of AGVs. In this paper, a manufacturing system with two types of AGVs and three types of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The exploration mode consists of two searches. The guided search toward the global best solution is formalized using (3) while the limited random search is formalized using (5). s c denotes the solution candidate which is then evaluated using (4) that represents the strict acceptance approach.…”
Section: Proposed Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The exploration mode consists of two searches. The guided search toward the global best solution is formalized using (3) while the limited random search is formalized using (5). s c denotes the solution candidate which is then evaluated using (4) that represents the strict acceptance approach.…”
Section: Proposed Modelmentioning
confidence: 99%
“…s c denotes the solution candidate which is then evaluated using (4) that represents the strict acceptance approach. In (5), it is shown that the local search space gets narrow as the iteration increases.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation